2018
DOI: 10.1002/celc.201800722
|View full text |Cite
|
Sign up to set email alerts
|

Electroanalytic Aspects of Single‐Entity Collision Methods for Bioanalytical and Environmental Applications

Abstract: entity electrochemistry based on measurements of collision events at electrode surfaces is a rapidly developing field which provides extensive capabilities for detection and characterization of a variety of materials including organic and inorganic nanoparticles (NPs) and nanostructures as well as biologicals. The method has demonstrated promising potential for the analysis of catalytic activity, physicochemical parameters, fundamental surface properties, functionalization and reactivity of NPs. Here, the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 120 publications
0
14
0
Order By: Relevance
“…[35][36][37][38][39][40][41] Especially, the electrochemical detection of single liposome collisions at UMEs is becoming an efficient and complementary tool for analyzing fundamental biological processes related to intracellular and extracellular electron transfers to discrete biological or artificial entities. [42][43][44] To explore the factors influencing the vesicles membrane permeability, we investigated the electrochemical and electrocatalytic reaction of different aqueous redox species (potassium ferrocyanide and cobalt(II) nitrate) encapsulated inside synthetic DMPC (1,2dimyristoyl-sn-glycero-3-phosphocholine) liposomes subjected to different experimental conditions (addition of surfactant, increase of temperature or presence of a redox probe in solution), by single collision detection on 10 μm diameter UMEs (Pt and carbon) as illustrated in Figure 1. We discuss the effect of the solution temperature on the liposome collision, its membrane rupture, and subsequent electrolysis of its redox content.…”
Section: /19mentioning
confidence: 99%
See 1 more Smart Citation
“…[35][36][37][38][39][40][41] Especially, the electrochemical detection of single liposome collisions at UMEs is becoming an efficient and complementary tool for analyzing fundamental biological processes related to intracellular and extracellular electron transfers to discrete biological or artificial entities. [42][43][44] To explore the factors influencing the vesicles membrane permeability, we investigated the electrochemical and electrocatalytic reaction of different aqueous redox species (potassium ferrocyanide and cobalt(II) nitrate) encapsulated inside synthetic DMPC (1,2dimyristoyl-sn-glycero-3-phosphocholine) liposomes subjected to different experimental conditions (addition of surfactant, increase of temperature or presence of a redox probe in solution), by single collision detection on 10 μm diameter UMEs (Pt and carbon) as illustrated in Figure 1. We discuss the effect of the solution temperature on the liposome collision, its membrane rupture, and subsequent electrolysis of its redox content.…”
Section: /19mentioning
confidence: 99%
“…Furthermore, it is well established that the liposome membrane stability is strongly dependent on its lipid composition and external parameters such as temperature and pH but also depends on interactions with specific molecules able to weaken, permeabilize, and penetrate the lipid bilayer following different pathways. An understanding of these different interactions and especially the mechanism leading to the lipid membrane opening is still an active research field. To this end, chronoamperometry is a useful method to probe the liposomes membrane permeability and to understand vesicle fusion processes onto electrode surface. Especially, the electrochemical detection of single liposome collisions at UMEs is becoming an efficient and complementary tool for analyzing fundamental biological processes related to intracellular and extracellular electron transfers to discrete biological or artificial entities. …”
mentioning
confidence: 99%
“…The SPCE technique measures single-impact events of a nano-entity colliding with the working microelectrode and monitoring current changes at a fixed potential value, which can be related to the size, coating, concentration, and redox state of that entity. 25 The method has been used to study a variety of entities including small inorganic NPs (e.g., Ag, Pt, and CeO 2 ), organics, 26 polymer capsules, 27 and biologicals. 28 We previously demonstrated that silver nanoparticles (AgNPs) are an effective electroactive probe for monitoring the structural characteristics of NP stabilizers and conformational changes of biological molecules assembling at their surface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…They offer, for instance, a clear distinction between the signal and background, a theoretical LOD of a single entity, and an increasing precision with recording time . Hence, stochastic electrochemistry-based sensors could open up entirely new opportunities and may provide calibration curves at subfemtomolar levels in the future. Recently, various groups successfully applied the concepts of stochastic electrochemistry in environmental and biosensing applications. Particularly in diagnostics, the early detection of very dilute disease markers is of outstanding interest. However, to apply stochastic electrochemistry as a reliable digital (bio)­sensor, several issues have to be addressed .…”
Section: Introductionmentioning
confidence: 99%